<em>x = - 9</em>
- Step-by-step explanation:
<em>6x + 10 = 4x - 8</em>
<em>6x - 4x = - 10 - 8</em>
<em>2x = - 18</em>
<em>x = - 18 : 2</em>
<em>x = - 9</em>
I drew these, as I just did these in math not too long ago. When I shaded it, it was in all four quadrants.
Answer:
a. 4r² b. 2r c. 6 cm
Step-by-step explanation:
The surface area A of the cube is A = 24r². We know that the surface area, A of a cube also equals A = 6L² where L is the length of its side.
Now, equating both expressions, 6L² = 24r²
dividing both sides by 6, we have
6L²/6 = 24r²/6
L² = 4r². Since the area of one face is L², the polynomial that determines the area of one face is A' = 4r².
b. Since L² = 4r² the rea of one face of the cube, taking square roots of both sides, we have
√L² = √4r²
L = 2r
So, the polynomial that represents the length of an edge of the cube is L = 2r
c. The length of an edge of the cube is L = 2r. When r = 3 cm.
L = 2r = 2 × 3 cm = 6 cm
So, the length of an edge of the cube is 6 cm.
Answer:
10 points the explantion is below
Step-by-step explanation:
Bob scored 35 points and Lilla scores 15 less so you start with 35 - 15. Then you want to divide 20 by 2 because Carol scored half as much as Lilla. Your equation is ( 35-15) / 2 = 10
Answer:
2
(
n
+
2
)
(
n
+
1
2
)
Step-by-step explanation:
coefficient of the first term:
2
=
2
×
1
coefficient of the last term:
2
=
2
×
1
coefficient of the middle term (using only the factors above):
5
=
2
×
2
+
1
×
1
2
n
2
+
5
n
+
2
=
(
2
n
+
1
)
(
n
+
2
)
Alternative method:
Treat the given expression as a quadratic set equal to zero, with the form
a
n
2
+
b
n
+
c
and use the quadratic formula
−
b
±
√
b
2
−
4
a
c
2
a
This will given solutions
n
=
−
2 and n
=
−
1
2
for a factoring
2
(
n
+
2
)
(
n
+
1
2
)
Hope this helped